Causal risk factors for asthma in Mendelian randomization studies: A systematic review and meta‐analysis. Issue 11 (7th November 2022) - Mikkelsen, Heidi; Landt, Eskild Morten; Benn, Marianne; Nordestgaard, Børge Grønne; Dahl, Morten
Abstract: Background: Several risk factors for asthma have been proposed; however, the causality of these associations is sometimes unclear. Mendelian randomization is a powerful epidemiological approach that can help elucidate the causality of risk factors. The aim of the present study was to identify causal risk factors for asthma through Mendelian Randomization studies. Methods: A systematic search of PubMed and EMBASE was conducted, to identify studies investigating risk factors for asthma or respiratory allergies through Mendelian Randomization. When two or more studies investigated the same risk factor a meta‐analysis was conducted. Of 239 studies initially identified, 41 were included. Results: A causal association between adiposity and adult asthma risk was found in 10 out of 12 studies with a summary risk ratio of 1.05 per kg/m 2 increase in BMI (95% CI: 1.03–1.07). Puberty timing ( n  = 3), alcohol ( n  = 2), and linoleic acid ( n  = 1) had causal effects on asthma risk, while vitamins/minerals ( n  = 6) showed no consistent effect on asthma. The effect of smoking on adult asthma conflicted between studies. Several of the significant associations of asthma with immune related proteins ( n  = 5) and depression ( n  = 2) investigated through multiple traits analyses could generally benefit from replications in independent datasets. Conclusion: This systematic review and meta‐analysis found evidence for causal effects of adiposity, puberty timing, linoleic acid, alcohol, immune related proteins, and depression on risk of asthma.